Varieties of Democracy Dataset - Version 10 - Coder-Level - Coppedge, Michael; Gerring, John; Knutsen, Carl Henrik; Lindberg, Staffan I.; Teorell, Jan; David, Altman; Bernhard, Michael; Fish, M. Steven; Glynn, Adam; Hicken, Allen; Lührmann, Anna; Marquardt, Kyle L.; et al. (University of Gothenburg, 2020)
Varieties of Democracy (V-Dem) is a new approach to conceptualizing and measuring democracy. We provide a multidimensional and disaggregated dataset that reflects the complexity of the concept of democracy as a system of rule that goes beyond the simple presence of elections. The V-Dem project distinguishes between five high-level principles of democracy: electoral, liberal, participatory, deliberative, and egalitarian, and collects data to measure these principles.

V-Dem draws on theoretical and methodological expertise from its worldwide team to produce data in the most objective and reliable way possible. Approximately half of the indicators in the V-Dem dataset are based on factual information obtainable from offcial documents such as constitutions and government records. The other half consists of evaluative indicators on topics like political practices and compliance with de jure rules. On such issues, typically five experts provide ratings. V-Dem works closely with leading social science research methodologists and has developed a state of the art Bayesian Item Response Theory measurement model that, to the extent possible, minimizes coder error and addresses issues of comparability across countries and over time. V-Dem also draws on the team’s academic expertise to develop theoretically informed techniques for aggregating indicators into mid- and high-level indices. In this sense, V-Dem is at the cutting edge of developing new and improved methods of social science measurement.

Varianter på demokrati (V-Dem) är ett internationellt forskningsprojekt vars syfte är att ta fram nya indikatorer på demokrati, i alla världens länder från år 1789 fram till idag. V-Dem erbjuder ett nytt sätt att konceptualisera och mäta demokrati, och särskiljer mellan fem demokratiprinciper: val-, liberal-, deltagar-, deliberativ- och jämlikhetsdemokrati, och samlar in data för att mäta dessa.
Varianter på demokrati Dataset - Version 10 - Kodare-Nivå
Keywords: elections; val; mass media; massmedia; social inequality; social ojämlikhet; election data; valdata; democracy; demokrati; corruption; korruption; political parties; politiska partier; democratization; demokratisering; heads of government; regeringschefer; heads of state; statschefer; electoral issues; valfrågor; media literacy; mediekunskap; mass media bias; mediavinkling; mass media use; mediaanvändning; sovereignty; suveränitet; legislature; lagstiftande församling; Social Media; Sociala medier; state; stat; equality between the sexes; lika rättigheter för män och kvinnor; Government, political systems and organisations; Regering, politiska system och organisationer; Political Science; Statsvetenskap; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)